Computer control of independently focused antenna with adaptive polarization - Ільницький, Л. Я.; Щербина, О. А. (Problems of Informatization and Control, 2005)
The independently focused antenna of adaptive polarization is considered. It can adapt itself to polarization of the electromagnetic wave and focus itself in the direction, from which the wave come